Factors related to outcome of early and delayed prosthetic joint infections. Issue 1 (January 2015) - Ascione, T.; Pagliano, P.; Mariconda, M.; Rotondo, R.; Balato, G.; Toro, A.; Barletta, V.; Conte, M.; Esposito, S.
Summary In this prospective study, we evaluate the impact of adherence to a diagnostic and therapeutic protocol on prosthetic joint infections (PJI) diagnostic accuracy and outcome. Patients and methods Patients with early or delayed PJI referred over a 5-year period were included. Diagnosis was based on characteristic clinical signs, radiographic findings and microbiological evidence. Antibiotics were chosen on the basis of microbiological findings, and drugs active against methicillin-resistant staphylococci were administered if no microbiological evidence had been obtained. Results Inclusion criteria were met in 159 cases (median age 64 years, males 45%). 56 were early infections and 103 delayed infections. Comorbidities were reported in 99 (62%) cases. Positive cultures were obtained in 122/159 (77%), coagulase-negative staphylococci were cultured in 20%, Staphylococcus aureus in 28%, and Pseudomonas aeruginosa in 7%. In early infections, cure rate after debridement and antibiotic therapy was 80%. In delayed infections, cure rate after two-stage exchange was 85%. Of 28 patients with delayed infection treated with antibiotics without surgery, only 8 (29%) infections were suppressed 48 weeks after treatment discontinuation. Rifampin afforded a better outcome. Conclusion Appropriate diagnostic and surgical procedures and microbiologically driven antibiotic therapy including rifampin are recommended to improve diagnostic accuracy and outcome.